Phytochemical, Antidiabetic and Therapeutic Properties of Zygophyllum - Zohra Mohammedi * (Lorestan University of Medical Sciences, 2021)
Natural bioactive compounds, isolated from medicinal plants, have an efficient role in the management of various diseases. They have remained sources of new drugs with diversified structural arrangements and interesting biological activities. Among these medicinal plants, species belonging to the genus Zygophyllum are efficient sources of bioactive compounds, mainly antihyperglycemic substances. Hence, they are used in traditional medicine against diabetes. It has been indicated that these species could be useful against the skin, stomach and liver diseases. The present review provides phytochemical profiles and in vitro as well as in vivo biological activities of a number of Zygophyllum plants with hypoglycemic properties, available through  researches from the selected research articles and books published from 1939 to 2017. The sources were collected from various databases.